Model Desain Sistem Instruksional Berorientasi Pencapaian Kompetensi (DSI-PK) dalam Perencanaan Pembelajaran : Tinjauan Literatur - Suci Isnaini; Sri Marmoah (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the application of the Competency Achievement-Oriented Instructional System Design (DSI-PK) model in learning planning. The problems faced by teachers are difficulties in designing learning that is appropriate to the characteristics of students, conducting assessments, and understanding the curriculum, so that learning planning is not optimal. This study uses a literature study method by reviewing various references related to the definition, characteristics, stages, supporting factors, inhibiting factors, and implementation of the DSI-PK model. The results show that DSI-PK has simple, coherent, and practical characteristics, with three main stages: needs analysis, development, and development of evaluation tools. Supporting factors include the availability of infrastructure, principal policies, and support from the school community, while obstacles include limited teacher understanding, assessment complexity, low student motivation, and limited facilities. Thus, DSI-PK can be a systematic solution in effective, measurable, and competency-oriented learning planning.